Economic Analysis of Regional Versus General Anesthesia for Hip Fracture Surgery - Mohseni, Masood (Annals of Anesthesiology and Critical Care, 2016)
Background: The economic burden of the treatment of hip fracture would be enormous, especially in countries like Iran with an aging population and limited financial resources. The choice of anesthetic technique for hip fracture surgery is controversial. We conducted this retrospective 4 year study to evaluate the effect of regional versus general anesthesia on the length of hospital stay and the cost of hospitalization in an academic governmental setting. Methods: We reviewed the medical records of 751 adult patients who underwent a surgery for intertrochanteric or femoral neck fracture since 2008 to 2012 in a University hospital located in Tehran, Iran. Data regarding days of hospital stay and total direct hospitalization costs as well as patients’ demographics were analyzed based on the type of planned anesthesia. The source of data collection was local electronic database. Results: Neuraxial anesthesia was associated with less hospital stay and costs in patients with intertrochanteric fracture surgery. The advantage of neuraxial over general anesthesia was not statistically significant in patients with femoral neck fracture. Conclusions: Neuraxial anesthesia followed by meticulous postoperative pain control may reduce the hospitalization period and costs of hip fracture treatment. This is especially true for the patients with intertrochanteric fracture.